Psychology: Where history, culture, and biology meet. (February 2023) - Newton, Tim
This article argues that the same epistemological assumptions cannot be confidently applied in the transition from the biological to the social arenas of psychology, as a consequence of the sociocultural instability resulting from human linguistic and technological flair. To illustrate this contention, reference is made to historicist theses within critical and sociocultural psychology, the work of Ian Hacking and Norbert Elias, the centrality of language and technology to sociocultural instability, and the illustrative issues raised by cultural neuroscience and replication studies.